THE IMPLEMENTATION OF COLLABORATIVE STRATEGY WITH INTEGRATED WRITING SKILLS IN ENGLISH LANGUAGE CLASSROOM AT MERCUBUANA UNIVERSITY - budiarto budiarto (Journal of English Language and Literature (JELL), 2017)
The purpose of this study is to investigate on how the teaching of integrated writing skills can be implemented through collaborative strategy. Writing skills need to be combined with other skills, because students need a lot of reading in order to obtain information, ideas and examples of correct writing. On the other hand feedback and ideas can also be gained by listening to what the teacher or a friend says. Fellow students can also discuss their writing and work together to develop ideas, discuss the use of grammar, the right words and rules in writing. Since writing skills requires a lot of rules and a long process, the collaboration is expected to reduce the burden experienced by the students. However, teachers should ensure that the collaboration is actually done by students properly by observing their activity, participation, and motivation in writing. Peer-reviewing activities can be used to monitor on how students actively engage in the writing process. Research was conducted at Mercubuana University is a qualitative research that focuses on how a lecturer teaches the students writing skills as an integrated skill, how she facilitates students to actively participate in collaborative writing, and how effectively she encourages the students to do peer reviewing.